Undergraduate students’ perception and satisfaction regarding online learning system amidst COVID-19 Pandemic in Pakistan - Ansar, Farrukh; Ali, Waqar; Khattak, Almas; Naveed, Hira; Zeb, Shah (Journal of Ayub Medical College Abbottabad, 2021)
Background: During COVID-19 pandemic, to forestall the outspread of contagion, all academic activities where physical presence was mandatory were halted. This prompted the shifting of educational activities to the online learning system. Current investigation aimed to determine the perception of undergraduate students of various disciplines about online learning which has been implemented across all the universities of Pakistan in the wake of COVID-19 lockdown. Methods: A cross-sectional descriptive study was conducted and data was collected from ten different medical, engineering and art universities of Pakistan. Utilizing Openepi, the calculated data sample size was 600. Students were asked 23 different questions including a validated and reliable scale (Î±=0.952) composed of 14 questions to determine the satisfaction level of students from e-learning. Descriptive statistics, independent sample t-test, ANOVA and chi-square test were used to analyse data through SPSS. Results: The most broadly embraced teaching methodology was online classes through Zoom Application. According to the developed scale, overall, 78% of students were dissatisfied from online learning. Students also raised concerns over assessment methods, student-instructor communication, fairness of examination and difficulty in understanding concepts. Majority of students preferred classroom teaching and 81% of respondents didn’t want to continue with e-learning. Conclusion: Results have depicted that students are not satisfied with e-learning and they pointed out some critical defects in the system. HEC and rectors should treat this issue as top-priority for provision of good quality education and to save the future of undergraduate students of Pakistan. Keywords: COVID-19; Education; E- Learning; Perceptions; Pakistan